Experimental Demonstration of Self-Oscillation Microcomb in a Mode-Splitting Microresonator - Wang, Xinyu; Xie, Peng; Wang, Yang; Wang, Weiqiang; Wang, Leiran; Little, Brent E.; Chu, Sai Tak; Zhao, Wei; Zhang, Wenfu (Frontiers in Physics, 2022)
Self-oscillation and bifurcation as many body dynamics solutions in a high-Q microresonator have induced in substantial interest in nonlinear optics and ultrafast science. Strong mode coupling between clockwise (CW) wave and counterclockwise (CCW) wave induce mode-splitting and optical self-oscillation in the optical cavity. In this letter, we experimentally demonstrate the self-oscillation microcomb formation in a microresonator with strong backward Rayleigh scattering. When a pump laser sweeps across a resonance, both spontaneous symmetry breaking and self-oscillation phenomenon are observed. The breathing soliton and stable soliton state can switch to each other through carefully tuning the pump detuning. Our experiments provide a reliable scheme for breather soliton microcomb generation. Meanwhile, the rich physics process enhances the comprehension on nonlinear optics in a cavity.